Dampak artificial intellligence terhadap perkembangan peserta didik - Zahwa Azahra Putri Azahra Putri; Arinda Hayu Nur Hasanah; Primarestya Putri Sea Wibagya; Prawati Ningsih (Universitas PGRI Madiun, 2026)
The rapid development of Artificial Intelligence (AI) has brought significant changes to various sectors, including education. AI-based technologies such as intelligent tutoring systems, adaptive learning platforms, and automated feedback tools are increasingly used to support the teaching and learning process. This study aims to examine the impact of AI on the development of students from cognitive, affective, and digital-skill perspectives through a theoretical review and literature study. The method used is a Systematic Literature Review (SLR), by collecting and analyzing national and international articles published between 2019 and 2025 obtained from Google Scholar, DOAJ, ERIC, and Sinta databases. The results show that AI provides positive contributions in improving learning outcomes, motivation, and digital literacy of students, while also posing challenges such as dependency, reduced critical thinking, and unequal access to technology. This study concludes that the effectiveness of AI in supporting students' development strongly depends on wise and balanced pedagogical implementation